Types of Code-switching Used by Multilingual Person on Youtube Channel - Rozillah, Rozillah; Hamzah, Hamzah (English Language and Literature, 2021)
This research is aimed in finding the types of code-switching used by Jang Hansol on Korea Reomit youtube channel. The data for this study are utterences used by Jang Hansol within his conversation from seven videos uploaded in Korea Reomit youtube channel. Romaine’s (1995) theory is applied in this research. The result of this study shows that the emergence of Inter-sentential between Indonesian to English was the most common type of code switching. This research gives the contribution in sociolinguistics fields. It is because the result of this study shows the relation of language and society. The used of code-switching by Hansol as the speaker in the conversation shows the relationship between him and the participants. So, It influenced the speaker’s choice of language in the conversation.